A new biocompatible COF-MCM nanoporous hybrid DDS for pH-controlled delivery of curcumin - R. Foulady-Dehaghi; Sh. Sohrabnezhad; M. Hadavi (Scientific Reports)
Abstract A novel polyimide-bridge covalent organic framework-based (PI-COF) hybrid was synthesized through simple green chemistry between PI-COF and MCM-NH2 monomers as a pH-sensitive anticancer curcumin (C) delivery system. The synthesized nanohybrid was crystalline in nature with an improved surface area and pore volume compared to the base COF, certified by powder X-ray diffraction spectroscopy and Brunauer–Emmett–Teller technique. Kinetically controlled and sustained curcumin release profiles were investigated using the as-prepared curcumin-loaded drug delivery systems (C@DDSs) in neutral and acidic pH media. C-loaded hybrid nanostructure prepared via the solvent-free drug loading process displayed a high entrapment efficiency (35.96%) and improved release in the acidic environment specific to cancer cells (pH = 4.5: 36.8%, pH = 7.4: 15.27%). In conclusion, we illustrated the utility of C@DDS as an in vitro drug delivery system in MDA-MB-231 cells. C@DDSs represented the time-dependent release of curcumin followed by cell death. Therefore, the reported PI-COF/MCM-NH2 system can be considered a new biocompatible carrier in COF research as a sensitive drug delivery system.